Absorption spectra of Nitrazine Yellow indicator. Experimental data and quantum chemical evaluations - Inna Khristenko; Volodymyr Ivanov (Вісник Харківського національного університету: Серія xімія)
This article presents an experimental investigation and theoretical analysis of the electronic absorption spectra of the indicator nitrazine yellow (NY) in aqueous solutions. Quantum chemical modeling of electronically excited states is performed within the framework of time-dependent density functional theory (TD-DFT). A variety of approaches and basis sets are explored, particularly focusing on the B3LYP and CAM-B3LYP functionals. The standard 6-31+G(d,p) basis set is employed, along with combinations using pseudopotential basis sets for Na and S atoms.